Termite-termite heterospeciﬁc cohabitation mediated by vibratory cues - Ferreira, Dinamarta Virginio (2023)
Distinct organisms can live together in intimate associations, called symbiosis. These heterospeciﬁc associations cover the entire spectrum, from parasitism to mutualism. Termite-termite heterospeciﬁc cohabitation is an interesting case of symbiosis. Several questions are raised to understand how hosts and inquilines remain living together sharing the same nest. For example, what are the main forces behind this phenomenon? In this context, we focused on two mechanisms: the ability to perceive and distinguish, as well as the process of becoming habituated to vibrations from heterospeciﬁc cohabitants. Here, we provide evidence that vibrations emitted by termites are an important communication channel used to perceive heterospeciﬁc vibrations. We found that cohabitation is shaped by a combination of inquiline and host behavioural characteristics. The ability to become habituated to heterospeciﬁc vibrations is a strong indication that both cohabitants do not perceive each other’s vibrations as a threat. Furthermore, the host species does not seek the source of vibration to ﬁnd the invader, allowing the maintenance of cohabitation. On the other hand, the inquilines can exhibit more distance travelled, independent of presence of vibrations, which would facilitate evasion when meeting the host. We show that the mechanisms linked to vibratory perception and habituation and a set of behavioural adaptations from the host and inquiline termites can facilitate cohabitation. Keywords: Termites. Cohabitation. Substrate-borne vibration. Habituation.